Elucidating crop losses and control of Rhizoctonia solani and Rhizoctonia cerealis in winter wheat - Brown, Matthew (2016)
Rhizoctonia solani is a species complex comprising 13 anastomosis groups (AG) that cause disease in a broad range of crops. Various AGs of R. solani are pathogenic to winter wheat causing damping-off and root rots. Rhizoctonia cerealis, the fungal agent of sharp eyespot, is known to commonly occur on the stems of wheat as part of stem base disease complex (SBD) consisting also of eyespot and brown foot rot (BFR). Eyespot is caused by Oculimacula acuformis or O. yallundae and BFR is principally caused by Microdochium nivale or M. majus. The population dynamics of SBD pathogens are continually changing due to environmental and agronomic pressures. Therefore, information on the current population dynamics and factors that influence population changes can guide the implementation of effective control measures. Furthermore the presence and dynamics of Rhizoctonia spp. in English wheat crops has not been previously investigated and there is also limited knowledge on the yield losses associated with root and stem base rhizoctonia diseases in wheat. This work aimed to elucidate crop losses and control of R. solani and R. cerealis in English wheat crops. An investigation was conducted into the incidence and severity of root and stem base diseases and population dynamics of their associated pathogens in 102 English winter wheat crops. Crop losses and control of the main Rhizoctonia spp. identified in English wheat crops were further investigated in artificially inoculated field experiments. Additional characterisation of Rhizoctonia spp. was investigated using ITS sequencing, isolate pathogenicity and in vitro fungicide sensitivity experiments. The predominant AG of R. solani in English winter wheat crops identified in 63% of soil samples was AG 2-1 with the highest DNA concentrations found in soil where the previous crop was oilseed rape. This suggests that OSR in the rotation is selecting for AG 2-1. Field experiments showed that wheat was not a major host of AG 2-1 since the pathogen failed to cause significant effects on wheat growth and yield. Sharp eyespot co-occurred with eyespot and BFR in English wheat crops. In 2011/12 at GS 65-75 sharp eyespot symptoms and R. cerealis DNA were detected in 90 and 94% of crops, respectively. The population structure of R. cerealis in English wheat crops revealed all isolates belonged to the subgroup AG D-I. Sharp eyespot incidence and severity showed considerable season to season variation primarily due to environmental conditions with cool, wet and humid summer conditions favouring the disease. However, agronomy practices did not have a major influence on sharp eyespot and R. cerealis DNA in soil or in planta. In field experiments R. cerealis caused significant plant establishment losses, stem browning and reduction in grain yield of 8.5% in winter wheat. The pathogenicity of R. cerealis isolates to wheat was confirmed in controlled environment experiments where significant damping-off and stem browning on 10 day old wheat seedlings occurred. In this study root rot was not correlated with any pathogen and was likely caused by a complex of species. Root rot incidence and severity in English wheat fields and in field experiments showed a decreasing trend in both seasons. BFR was the predominant SBD in English wheat crops occurring in 100% of crops by GS 37 in both seasons. Eyespot showed season to season variation and was favoured by warm, wet and humid conditions in the spring. The causal agents of eyespot the Oculimacula spp. were the most common occurring species in the soil and in planta of English wheat crops. DNA of Oculimacula spp. and Microdochium spp. was detected in ≥90% of stem bases in both seasons, showing these species are ubiquitous in English wheat crops. Results indicated a shift in the Oculimacula spp. population in English wheat crops with both species occurring together although O. yallundae was clearly the predominant species in terms of biomass. Protecting plants in the establishment phase of development from Rhizoctonia spp. is critical as early infections can lead to seedling death. Seed treatments are considered the most effective way to target and deliver fungicides to control infections by Rhizoctonia spp. In field experiments sedaxane + fludioxonil provided more consistent control of damping-off and stem browning than fludioxonil alone. In addition, fungicide EC50 values to inhibit mycelial growth of R. solani and R. cerealis isolates were lower for sedaxane than fludioxonil or prothioconazole. Sedaxane + fludioxonil also significantly reduced BFR up to GS 39, but showed inconsistent control of sharp eyespot beyond GS 13. To conclude, this study has found that AG 2-1 is widespread in English wheats crops and this may have implications for the growth and development of OSR. Rhizoctonia cerealis was shown to significantly reduced emergence and grain yield of winter wheat. This suggests control of this pathogen should receive greater attention especially at the establishment phase of development and that seed treatments (i.e. sedaxane) are the most effective control option to protect seedlings.